Вплив строків внесення добрив на продуктивність сої в Степу України - Черненко, Карина Олександрівна; Chernenko Karyna (ЦНТУ, 2023)
В даній випускній кваліфікаційній роботі вивчається вплив строків внесення мінеральних добрив на продуктивність сої. Мета досліджень – встановити вплив строків внесення добрив на продуктивність ранньостиглого сорту сої Золушка. В умовах Степу України слід удобрення ранньостиглого сорту сої Золушка проводити розкидним способом навесні та інокуляцію насіння біопрепаратом Нітроген Квік. Це забезпечить врожайність 2,45 т/га, прибавку врожаю 0,25 т/га (11,4%), чистий дохід 25753 грн./га, рентабельність 162%. In this final qualification work, the influence of the terms of application of mineral fertilizers on the productivity of soybeans is studied. The purpose of the research is to establish the influence of the timing of fertilizer application on the productivity of the early-ripening soybean variety Zolushka. In the conditions of the Steppe of Ukraine, fertilization of the early ripening Cinderella soybean variety should be carried out by the spreading method in the spring and seed inoculation with the biological preparation Nitrogen Quick. This will ensure a yield of 2.45 t/ha, a yield increase of 0.25 t/ha (11.4%), a net income of UAH 25,753/ha, and a profitability of 162%.
The influence of fertilizer application dates on soybean productivity in the Steppe of Ukraine
Keywords: соя; строки внесення добрив; продуктивність; soybean; timing of fertilization; productivity